Jonathan Edwards’s Theology of Providence - Yoo, Bonghyun (My University, 2024)
Jonathan Edwards firmly embraced divine providence, shaping his spiritual, pastoral, and theological life. He yearned for revival, a glorious and wonderful working of divine providence. As a Puritan preacher in New England, Edwards devoted himself to highlighting the significance of divine providence to the congregations of his day. Edwards also considered God’s being and providence as fundamental concepts in his theological works. Edwards located his doctrine of providence within the doctrine of God (e.g., God as a communicative being), not as a subsection of the doctrine of creation, particularly emphasizing it with a trinitarian concept of deity. To him, providence comprised all divine activity ad extra and reflected the dynamic inner life of the Trinity. This dissertation argues that the triune Redeemer is the centre of reflection in Edwards’s theology of providence. The redemptive work of the Trinity was closely integrated into his understanding of providence, thereby maintaining the distinctive Christian meaning and character of the doctrine of providence. This trinitarianredemptive concept of providence in Edwards’s theology is a historically extended and socially embodied argument. Retrieving Edwards’s trinitarian theology of providence offers a remedy for the concept of providence in contemporary theology that has lost its trinitarian and redemptive dimension due to its failure to interface the work of the Trinity in redemption with that of providence.
A Trinitarian Account
Keywords: Jonathan Edwards; Trinity